Exploring synergistic effects: Atorvastatin and electrical stimulation in spinal cord injury therapy - Martina Magurova; Maria Bacova; Stefania Papcunova; Katarina Kiss Bimbova; Tomas Kuruc; Alexandra Kisucka; Lenka Ihnatova; Karolina Kucharova; Nadezda Lukacova; Jan Galik (IBRO Neuroscience Reports)
Spinal cord trauma represents a significant clinical challenge, and improving patient outcomes is a main priority for many scientific teams globally. Despite advances in the understanding its pathogenesis, the overall mechanisms occurring in the spinal cord after traumatic injury remain unclear. This study explores the possible synergistic effects of a regenerative therapy that combines electrical stimulation with the anti-inflammatory drug Atorvastatin (ATR) after spinal cord injury (SCI). SCI was induced at the T9 segment under isoflurane anesthesia and applying a compression force of 40 g for 15 minutes. An oscillating field stimulator (OFS) was implanted subcutaneously, delivering a weak electric current (50 µA) that changed polarity every 15 minutes for six weeks to promote axonal growth at the injury site. Female Wistar albino rats were divided into four groups: SCI with non-functional stimulator (SCI + nOFS), SCI with functional stimulator (SCI+OFS), and two groups that received ATR together with stimulator for 7 days after injury (SCI+OFS+ATR, SCI+nOFS+ATR). Behavioral tests (hot-plate test and BBB scale) showed improvement in sensory and motor performance in animals treated with the combination therapy. The protein levels of astrocytes (GFAP), neurofilaments (NF-L), newly sprouting axons (GAP-43), and oligodendrocytes (PLP −1, CNPase) were analysed by Western blot. The results showed increased neurofilaments, newly sprouting axons and oligodendrocytes in groups receiving both individual and combination therapies, with a decrease in their concentrations in the following order: SCI+OFS+ATR, SCI+nOFS+ATR, SCI+OFS, SCI+nOFS. In addition, astrocyte protein levels were lower in the SCI+OFS+ATR group compared with others. Histological analysis showed a significant reduction in white and gray matter after SCI, but less white and gray matter volume loss was found in the groups receiving therapies (SCI+OFS+ATR, SCI+nOFS+ATR, SCI+OFS). These results suggest that the combination of Atorvastatin with OFS stimulation promotes neural recovery after SCI, highlighting the potential of combination therapies in enhancing regenerative outcomes.